THE THEORETICAL FOUNDATIONS OF THE PROJECT PROCESS AT THE LEVEL OF THE TERRITORIAL COMMUNITY - Rychkina L.V. (Pressing Problems of Public Administration, 2015)
The article summarizes the main theoretical and methodological approaches to the conceptof “project”, the basic functions, principles of the project, the factors that influence the projectmanagement, presented a classification scheme of social projects and the process of the project.